A New Dog for pre-primary - Hunt,Roderick (Oxford university press)
"A New Dog" by Roderick Hunt is a delightful story from the Oxford Reading Tree series. In this book, the characters welcome a new dog into their lives, experiencing the excitement and challenges that come with a pet. As they adjust to having the dog around, they learn about responsibility, friendship, and the joy of caring for an animal. The story captures the playful interactions between the children and the dog, emphasizing themes of love and companionship. With engaging illustrations and a simple narrative, it's perfect for young readers exploring the joys of having a pet.
Keywords: Textbook